Microbiota and Antibiotic Resistome of Lettuce Leaves and Radishes Grown in Soils Receiving Manure-Based Amendments Derived From Antibiotic-Treated Cows - Fogler, Kendall; Guron, Giselle K. P.; Wind, Lauren L.; Keenum, Ishi M.; Hession, W. Cully; Krometis, Leigh-Anne; Strawn, Laura K.; Pruden, Amy; Ponder, Monica A. (Frontiers in Sustainable Food Systems, 2019)
Cattle are commonly administered antibiotics, resulting in excretion of antibiotics, antibiotic resistant bacteria (ARB), and antibiotic resistance genes (ARGs). The aim of this study was to determine if the use of dairy manure collected during antibiotic administration influences the bacterial microbiota of lettuce and radishes, including carriage of ARB and ARGs, when applied as a soil amendment and if composting mitigates the effects. Lettuce and radishes were grown in field-plots amended with raw manure from antibiotic-treated (cephapirin, pirlimycin) cows, composted manure from antibiotic-treated cows, composted manure from antibiotic-free cows, or an inorganic chemical fertilizer (control; 12 plots, n=3). Surficial vegetable bacteria and antibiotic resistomes (i.e., total ARGs) were characterized using heterotrophic plate counts (HPCs) on antibiotic-containing media, 16S rRNA gene amplicon sequencing, quantitative polymerase chain reaction (qPCR), and shot-gun metagenomics. The different manure and compost amendments did not result in significant changes to the surficial vegetable bacteria at the phylum level; however, some minor changes at the class and family level were observed. Beta-diversities of the ARGs detected by shotgun metagenomic sequencing were distinctly different between vegetable type (R=0.30, p=0.04), with small separations between the resistomes associated with amendment type in unrarified analysis (R=0.27, p=0.02), but not rarified analysis of the data. Network analysis highlighted multi-drug ARG classes commonly co-occurred with plasmid associated genes and could be a driver of co-and cross-selection of ARGs in the different conditions. Carriage of sul1 and tet(W) ARGs on vegetables quantified by qPCR were strong indicators of manure-based amendment relative to chemical fertilizer, with some reduction incurred via composting (p<0.05). Also, increased HPCs resistant/tolerant to clindamycin, a class of antibiotics administered to cattle, were on lettuce grown in biological soil amendments relative to chemical fertilizer (p<0.05). This study demonstrates that amending soil with raw manure collected from dairy cows during antibiotic administration may affect the composition of microbiota and resistome associated with vegetable surfaces. Composting may be an important strategy to reduce some ARGs on fresh produce, but differences in the resistomes of lettuce and radishes suggest the extent of soil contact should be considered.